Pengaruh Kepuasan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Unit Pengamanan Pada Pt Agung Rahardja Manunggal Yudha (Army) Di Gedung Capital Place Jakarta Selatan - Maya Nur Alfarizka; Risza Putri Elburdah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract - The purpose of this study was to determine the effect of job satisfaction and work discipline on employee performance of the security unit of PT Agung Rahardja Manunggal Yudha (ARMY) in the Capital Place Building, South Jakarta, partially and simultaneously. The method used is quantitative. The population in this study consisted of 150 employees. The sampling technique uses the Slovin formula and a sample of 109 respondents was obtained. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are that job satisfaction has a significant effect on employee performance with the regression equation Y = 16.397 + 0.578X1, a correlation coefficient value of 0.655 (strong), a determination coefficient of 43.0% and a hypothesis test obtained t count> t table or (8.978> 1.982). Work discipline has a significant effect on employee performance with the regression equation Y = 15.536 + 0.595X2, the correlation coefficient value is 0.644 (strong), the determination coefficient is 41.4% and the hypothesis test obtained t count> t table or (8.701> 1.982). Job satisfaction and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 7.822 + 0.403X1 + 0.402X2. The correlation coefficient value is 0.761 (strong), the determination coefficient is 58.0% while the remaining 42.0% is influenced by other variables. The hypothesis test obtained the F count value> F table or (73.103> 2.690).